Oxytocin‐monomeric red fluorescent protein 1 synthesis in the hypothalamus under osmotic challenge and acute hypovolemia in a transgenic rat line. Issue 17 (10th September 2020) - Ueno, Hiromichi; Sanada, Kenya; Miyamoto, Tetsu; Baba, Kazuhiko; Tanaka, Kentaro; Nishimura, Haruki; Nishimura, Kazuaki; Sonoda, Satomi; Yoshimura, Mitsuhiro; Maruyama, Takashi; Oginosawa, Yasushi; Araki, Masaru; et al.
Abstract: We generated a transgenic rat line that expresses oxytocin (OXT)‐monomeric red fluorescent protein 1 (mRFP1) fusion gene to visualize the dynamics of OXT. In this transgenic rat line, hypothalamic OXT can be assessed under diverse physiological and pathophysiological conditions by semiquantitative fluorometry of mRFP1 fluorescence intensity as a surrogate marker for endogenous OXT. Using this transgenic rat line, we identified the changes in hypothalamic OXT synthesis under various physiological conditions. However, few reports have directly examined hypothalamic OXT synthesis under hyperosmolality or hypovolemia. In this study, hypothalamic OXT synthesis was investigated using the transgenic rat line after acute osmotic challenge and acute hypovolemia induced by intraperitoneal (i.p.) administration of 3% hypertonic saline (HTN) and polyethylene glycol (PEG), respectively. The mRFP1 fluorescence intensity in the paraventricular (PVN) and supraoptic nuclei (SON) was significantly increased after i.p. administration of HTN and PEG, along with robust Fos‐like immunoreactivity (co‐expression). Fos expression showed neuronal activation in the brain regions that are associated with the hypothalamus and/or are involved in maintaining water and electrolyte homeostasis in HTN‐ and PEG‐treated rats. OXT and mRFP1 gene expressions were dramatically increased after HTN and PEG administration. The plasma OXT level was extremely increased after HTN and PEG administration. Acute osmotic challenge and acute hypovolemia induced upregulation of hypothalamic OXT in the PVN and SON. These results suggest that not only endogenous arginine vasopressin (AVP) but also endogenous OXT has a key role in maintaining body fluid homeostasis to cope with hyperosmolality and hypovolemia. Abstract : CVOs activation under hyperosmolality, and brainstem neurons and SFO activation under hypovolemia could upregulate OXT synthesis in the hypothalamus.